“We Can Be Pioneers” : Exploring experimental knowledge sharing in an online peer-support forum for non-offending pedophiles - Rask Pedersen, Mikkel (STS Encounters, 2021)
Online peer-support forums can enable those alienated from society to engage in experimental knowledge sharing practices in the absence of professional and public interaction. This, in turn, helps them manage problems in new ways. However, for pedophiles, it is unsure when peer-support help forum users cope in healthy ways, and when they justify harmful behaviors. The article argues, that exploring the potentials of peer-support forums for pedophiles to help combat child sexual abuse, this produces an analytical challenge to represent the users’ experimental knowledge sharing practices without tying them to the very categories they try to escape. To accommodate this challenge, the article proposes to view these practices as politically contingent experiments rather than fixed results, and uses Donna Haraway’s concept of situated knowledge to do so. Based on a grounded theory analysis of an observational and ethnographic fieldwork on the Virtuous Pedophiles online peer-support forum for non-offending pedophiles, the article proceeds to analyzes relations and networks between the users’ personal experiences and the political situation that surrounds. The results are discussed in relation to classical frameworks of experiments in STS. Finally, experimenting as a mode of practice and analytical tool is argued to contribute to child sexual abuse prevention research, due to its attention to performances, resistances, and constraints, important to understand the challenges of being a non-offending pedophile.